THE INFLUENCE OF DIGITAL CUSTOMER EXPERIENCE AND ENJOYMENT ON FLIP E-WALLET E-LOYALTY THROUGH E-TRUST IN MEDAN CITY MILLENIAL GENERATIONS - Fika Yusti Harahap; Amrin Fauzi; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The digital revolution has changed various business environments, including the financial services industry. In this era, a financial service that called financial technology has been developed. The existence of a digital revolution can present various kinds of innovations in digital payments, one of which is e-wallet. The existence of various e-wallets can lead to increasingly fierce competition to get customer e-loyalty. E-loyalty becomes a top priority in this research because e-loyalty plays an important role in creating a sustainable competitive advantage, so companies can develop better in the long term. The purpose of this study was to find out and analyze the effect of digital customer experience and enjoyment on e-loyalty, e-wallet flip through e-trust in the millennial generation in Medan city. The population in this study was all millennials who had used the Flip application in Medan city. The sampling method used the Non Probability Sampling technique with Purposive Sampling, while the number of samples in this study were 115 respondents. The data analysis method used Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that Digital Customer Experience has a positive and significant effect on E-Loyalty, Enjoyment has a positive and significant effect on E-Loyalty, Digital Customer Experience has a positive and significant effect on E-Trust, Enjoyment has a positive and significant effect on E-Trust, E- Trust has a positive and significant effect on E-Loyalty, Digital Customer Experience has a positive and significant effect on E-Loyalty through E-Trust, Enjoyment has a positive and significant effect on E-Loyalty through E-Trust.